The Role of Multitalented Teachers in Optimizing Students' Interests, Talents, and Learning Achievements at SMAN 1 Pringgarata - Ahmad Ali Jazali; Asnita; Aini Lestari; Farhuriah; Dinde Najwa Aira Salsabila; Edy Herianto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to identify the role of multitalented teachers in increasing the interest, talent, and learning achievement of students at SMAN 1 Pringgarata. As educators who have expertise in various fields, multitalented teachers are expected to create a more engaging learning atmosphere and provide opportunities for students to develop their potential optimally. The method used in this study is a qualitative approach with data collection techniques through in-depth interviews, observations, and documentation studies. The results of the study show that multitalented teachers can make a significant contribution in developing students' interests and talents through innovative learning approaches, the use of various media, and the provision of motivation and guidance that suits the needs of students. In addition, the diversity of teacher skills also plays a role in creating a learning environment that supports the achievement of students' academic achievements. This research suggests the importance of developing multi-talented competencies in teachers to support better quality education in schools.